2012
DOI: 10.3168/jds.2011-4823
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of whey proteins microparticulated at low pH

Abstract: The main aim of the study was to assess the effect of microparticulation at low pH on the functionality of heat-denatured whey proteins (WP). Spray-dried, microparticulated WP (MWP) powders were produced from 7% (wt/wt) WP dispersions at pH 3, acidified with citric or lactic acid, and microfluidized with or without heat denaturation. Nonmicroparticulated, spray-dried powders produced at neutral pH or pH 3 served as controls. The powders were examined for their functional and physicochemical properties. Denatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 30 publications
4
43
0
3
Order By: Relevance
“…This observation was in line with 187 the observations of an earlier study that showed enhanced heat stability of WP at low pH 188 (Dissanayake et al, 2012). The relatively low ∆H values of WP dispersion heated at pH 6 189 further indicated destruction of hydrophobic bonds, resulting in denaturation of WPs 190 (Damodaran, 2008) are clearly visible only in lane 3 ( Fig.…”
Section: Thermal Analysis Of Whey Protein Dispersions 181 182supporting
confidence: 79%
See 1 more Smart Citation
“…This observation was in line with 187 the observations of an earlier study that showed enhanced heat stability of WP at low pH 188 (Dissanayake et al, 2012). The relatively low ∆H values of WP dispersion heated at pH 6 189 further indicated destruction of hydrophobic bonds, resulting in denaturation of WPs 190 (Damodaran, 2008) are clearly visible only in lane 3 ( Fig.…”
Section: Thermal Analysis Of Whey Protein Dispersions 181 182supporting
confidence: 79%
“…Therefore, the inclusion of WPs into food systems is dependent on processing 48 conditions applied and their influence on protein structure that, due to the heat sensitivity of 49 WPs, may even result in complete denaturation and thus limit their application. Recently a 50 novel approach to stabilization of WPs through microparticulation was proposed 51 (Dissanayake & Vasiljevic, 2009;Dissanayake, Liyanaarachchi, & Vasiljevic, 2012) to 52 alleviate this problem. 53…”
Section: Introduction 36 37mentioning
confidence: 99%
“…Since whey proteins are relatively low molecular weight and soluble at its isoelectric point [13], a thermal treatment is necessary to precipitate them [14]. During this process, β-Lg (the major component of whey proteins) undergoes a structural change-exposes the S-S groups, which play a central role in the formation of covalent "bridges" with other proteins.…”
Section: Yield and Water Retention Of Protein Aggregatesmentioning
confidence: 99%
“…This method has been employed for years and used to produce low-moisture food products such as snacks and breakfast cereals. Another approach termed microparticulation has been used commercially to create whey protein-rich products with enhanced solubility at high temperatures (Dissanayake 2011 Milk is defined as the secretion of the mammary glands of mammals with the primary function to satisfy nutritional requirements of neonates. Milk of some animals, especially cows, buffaloes, goats, and sheep, is used for human consumption, either as such or in the form of a range of dairy products.…”
Section: Referencesmentioning
confidence: 99%